Hong Kong's Growth Synchronization with China and the U.S. : A Trend and Cycle Analysis - He, Dong (IMF Working Papers; Working Paper ;, 2015)
This paper investigates the synchronization of Hong Kong SAR's economic growth with mainland China and the United States. This paper identifies trends of economic growth based on the permanent income hypothesis. Specifically, the paper confirms whether real consumption in Hong Kong SAR and mainland China satisfy the permanent income hypothesis, at least in a weak form. It then identifies the permanent and transitory components of income of each economy using a simple state-space model. It uses structural vector autoregression models to analyze how permanent and transitory shocks originating from mainland China and the United States affect the Hong Kong economy, and how such influences evolve over time. The paper's main findings suggest that transitory shocks from the United States remain a major driving force behind Hong Kong SAR's business cycle fluctuations. On the other hand, permanent shocks from mainland China have a larger impact on Hong Kong SAR's trend growth.